CGIAR and partner Gender Researchers Unite for transformative practices - Bailey, Arwen; Rietveld, Anne (2024)
The innovation is a Community of Practice for gender researchers of CGIAR and their research partners in universities and National Agriculture Research (NAR) institutes. Gender researchers have a multiplying effect, improving the gender-transformative potential of the research that they do in the initiatives and bilateral projects throughout CGIAR.